1992
DOI: 10.1038/clpt.1992.23
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between paroxetine and the sparteine oxidation polymorphism

Abstract: The relationship between the selective serotonin reuptake inhibitor paroxetine and the sparteine oxidation polymorphism was investigated in a combined single-dose (30 mg) and steady-state (30 mg/day for 2 weeks) study including a panel of nine extensive metabolizers and eight poor metabolizers of sparteine. The median area under the plasma concentration-time curve (AUC) after the first paroxetine dose was about seven times higher in poor metabolizers than in extensive metabolizers (3910 versus 550 nmol.hr/L), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(106 citation statements)
references
References 7 publications
2
103
0
1
Order By: Relevance
“…29 Consequently, CYP2D6 is considered as a 'high affinity-low capacity' metabolic clearance pathway. 30 Consistent with this, the contribution of CYP2D6 to disposition of antipsychotics and other substrates is comparatively reduced during multiple [30][31][32][33][34] vs single-dose 31,35 drug administration. A considerable overlap in the distribution of antipsychotic serum concentration between EMs and PMs of CYP2D6 was also noted during chronic treatment.…”
Section: Introductionmentioning
confidence: 53%
“…29 Consequently, CYP2D6 is considered as a 'high affinity-low capacity' metabolic clearance pathway. 30 Consistent with this, the contribution of CYP2D6 to disposition of antipsychotics and other substrates is comparatively reduced during multiple [30][31][32][33][34] vs single-dose 31,35 drug administration. A considerable overlap in the distribution of antipsychotic serum concentration between EMs and PMs of CYP2D6 was also noted during chronic treatment.…”
Section: Introductionmentioning
confidence: 53%
“…In addition, it was shown that activity with respect to CYP2D6 phenotype could affect the exposure of paroxetine in children and adolescents (Findling et al, 1999). These phenomena have also been reported in adults (Ozdemir et al, 1999;Sindrup et al, 1992b) and are due to the involvement of the saturable enzyme CYP2D6 in paroxetine clearance.…”
Section: Introductionmentioning
confidence: 88%
“…PMs have no functional CYP2D6 enzyme as a result of mutations in the CY P2D6 gene. Interestingly, the phenotypic difference in paroxetine clearance is less after multiple dosing [6], presumably due to the development of inhibition and/or saturation of CYP2D6 in extensive metabolizers (EMS). CYP2D6 also makes a minor contribution to the N-demethylation of both enantiomers of fluoxetine, as indicated by studies using microsomes of human liver and of cells expressing CYP2D6 cDNA [ 131.…”
Section: Introductionmentioning
confidence: 99%
“…Two other SSRI agents, fluvoxamine and citalop-150 S. I/. Otton et al ram have K , values of 2 to 2 0 p~, and are weak inhibitors of CYP2D6 activity in uivo [ 10, 111. In addition to inhibiting CYP2D6, paroxetine is also metabolized by this enzyme [6,121 and the pharmacokinetics of paroxetine are altered in the 7% of Caucasians who are poor metabolizers (PMs). PMs have no functional CYP2D6 enzyme as a result of mutations in the CY P2D6 gene.…”
Section: Introductionmentioning
confidence: 99%